Divulgação da década das ciências oceânicas na costa paraense através da aplicação de uma sequência didática. - MOTA, Lucílio Lopes (Universidade Federal do Pará, 2024)
The Pará state coast is formed by a rich mosaic of ecosystems, predominantly consisting of sandbanks and mangroves influenced by the Amazon River, as well as channels and islands. The region boasts high biodiversity and requires urgent protection due to environmental impacts such as siltation, erosion, overfishing, and mangrove depletion. In this context, the United Nations (UN) launched the Decade of Ocean Science for Sustainable Development (Ocean Decade - 2021 to 2030), with a focus on Sustainable Development Goal 14 (Life Below Water) of the 2030 Agenda. However, a pressing issue observed today relates to anthropogenic pressure and its consequences on the coastal zone. With the aim of promoting sustainable ocean education for public schools in the region, we employed a qualitative-quantitative methodology in the municipality of São João da Ponta, taking advantage of the regional specificity. For the project's purpose, the ocean was pedagogically and didactically used as a generative theme in the Freirean language in the classroom, always seeking to connect it to the students' reality in the adjacent coastal zone. To validate the research, we developed a booklet on ocean culture, used within a didactic sequence inspired by original UNESCO materials but adapted to the coastal ocean culture of the region. In the classroom, a questionnaire with 10 questions on ocean-related topics was administered before and after the execution of the lessons. Two 9th-grade classes (A and B) from the same school were chosen, with one class having the questionnaire and six lessons, and the other class having the questionnaire and the same lessons with the support of the ocean culture booklet. After a statistical analysis of the questionnaires answered by the classes, it was observed that in Class A, where the booklet was introduced, occurred there was a significant increase in correct answers compared to Class B. This indicated a positive relationship between the use of the booklet in lessons as a fundamental tool for teaching and promoting awareness of the Decade of Ocean Science.